2021
DOI: 10.3390/ijms222011034
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and Melatonin Biosynthesis in Plants: Genome-Wide Identification of the Genes and Their Expression Reveal a Conserved Role in Stress and Development

Abstract: Serotonin (Ser) and melatonin (Mel) serve as master regulators of plant growth and development by influencing diverse cellular processes. The enzymes namely, tryptophan decarboxylase (TDC) and tryptamine 5-hydroxylase (T5H) catalyse the formation of Ser from tryptophan. Subsequently, serotonin N-acetyl transferase (SNAT) and acetyl-serotonin methyltransferase (ASMT) form Mel from Ser. Plant genomes harbour multiple genes for each of these four enzymes, all of which have not been identified. Therefore, to delin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 84 publications
3
54
0
Order By: Relevance
“…This is further evident by an increase in the melatonin content in unprimed stressed plants of the tolerant variety. However, the decrease in melatonin content in tolerant primed stressed plants compared to unprimed stressed plants (Figure 2) signify the feedback inhibition, which is consistent with findings of Bhowal et al (2021). Further, down-regulated expression of T-5H and ASMT in this variety (Supplementary Figures 3B, D) also correlated to the decreased endogenous melatonin content.…”
Section: Exogenous Priming Increases Endogenous Melatonin Contentsupporting
confidence: 82%
“…This is further evident by an increase in the melatonin content in unprimed stressed plants of the tolerant variety. However, the decrease in melatonin content in tolerant primed stressed plants compared to unprimed stressed plants (Figure 2) signify the feedback inhibition, which is consistent with findings of Bhowal et al (2021). Further, down-regulated expression of T-5H and ASMT in this variety (Supplementary Figures 3B, D) also correlated to the decreased endogenous melatonin content.…”
Section: Exogenous Priming Increases Endogenous Melatonin Contentsupporting
confidence: 82%
“…We only found one study regarding the role of miRNAs in regulating melatonin biosynthesis genes. Recently, Bhowal et al (2021) reported that miR6249a and miR1846e regulated the expression of serotonin and melatonin biosynthesis under heat, salinity, and drought stress by influencing the expression of TDC5 and ASMT18 , respectively. Our results provide evidence that partially sheds light on some attributes of this causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Its homologous gene in Arabidopsis (AT4G35160, or acetyl serotonin methyltransferase ASMT1 , Berardini et al, 2015 ) has been reported to be expressed in the epidermal L1 layer in the shoot apex. The melatonin biosynthesis pathway was recently shown to be associated with both abiotic ( Wang et al, 2021 ) and biotic ( Zhu et al, 2021 ) stress responses ( Bhowal et al, 2021 ). Members of the melatonin pathway have been shown to be involved in responses to osmotic, drought, and heat stresses ( Bhowal et al, 2021 ), and many of these genes are regulated through miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The melatonin biosynthesis pathway was recently shown to be associated with both abiotic ( Wang et al, 2021 ) and biotic ( Zhu et al, 2021 ) stress responses ( Bhowal et al, 2021 ). Members of the melatonin pathway have been shown to be involved in responses to osmotic, drought, and heat stresses ( Bhowal et al, 2021 ), and many of these genes are regulated through miRNAs. In rice, induction of the homologous gene, OsASMT1 , occurred following exposure to the cytokinin benzylaminopurine ( Bhowal et al, 2021 ) which is known to stimulate cell division.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation